A Computational Study of the Chemomechanics of Paracetamol Polymorphs: Towards Improving Drug Tabletability - Samra, Karim Nader (AUC Knowledge Fountain, 2026)
The mechanical properties of pharmaceutical crystals are of great importance in tablet manufacturing. Also, knowing the mechanical properties of different polymorphs of the same crystal can reduce the overall production cost. In this study, computational work was done via performing density functional theory calculations on 3 paracetamol crystal polymorphs Form I, II, and III. Understanding the chemical bonding helps in predicting the key elastic properties for different crystallographic directions. In Form II, lattice vector C is dominated with the intermolecular hydrogen bond OH…O giving it the stiffest Young Modulus and the least Poisson’s ratio. Then comes the A-Axis which contains the intermediate strength intermolecular hydrogen bond NH…O, and lastly, the B-Axis which is dominated by weak van der Waals leading to the least stiffness and the largest Poisson’s ratio. Overall, this gives a ranking as follow: C (OH…O) > A (NH…O) > B (van der Waals) in Form II and B (OH…O) > A (NH…O) > C (van der Waals) for Form III. In Form I none of the principal crystallographic directions (A, B, and C) is controlled by a single type of intermolecular bonding and hence no similar chemomechanical trends can be elucidated. This work also resolves the contradiction in literature regarding which form among I and II is more compressible. Under hydrostatic compressions, we found out that Form I is more compressible than Form II along two crystallographic directions (A and B). However, the C-Axis of Form I starts to expand with continued applied pressure leading to an overall bulk modulus for Form I that is comparable to Form II. Thus, in an average sense Form II is as compressible as form I, meanwhile in an anisotropic sense, Form I is more compressible in certain key directions. Moreover when Form III is included in this comparison the overall ranking in bulk becomes : Form III < Form II ~ Form I. We believe that for grains of Form II and I under tableting pressing conditions, the predictions of which Form will exhibit net easier compressibility depends on the nature of the net applied stress (hydrostatic vs. axial) and also on the texture and porosity of the grains. We suggest future finite element modeling efforts to address this problem. Lastly, we compared evaluating the elastic properties of the three forms using two different computational approaches: the brute-force calculations of stress-strain curves and 2nd order elastic constants. The elastic constants approach agrees well with the findings in brute-force approach in terms of the magnitudes of the elastic properties and the chemomechanical trends discussed above. This gives credibility to the 2nd order elastic constants which also has the added advantage of its ability to explore the elastic properties of all crystallographic directions with simple analytical formulas. Furthermore, the elastic constants approach revealed that Form III is mechanically unstable in crystallographic directions different than the principal ones (other than A, B, C). This instability would be difficult to probe using brute-force stress-strain calculations since this computation is expensive and hence cannot be conducted in random directions. The detailed analyses and data presented in this work for an important drug such as Paracetamol are aimed to be a future reference for developing a computational framework that aims to enhance drug tabletability and generally, pharmaceutical manufacturing.